Effectiveness of interpretive exhibits at Brown v. Board of Education National Historic Site - Stork, Lisa (Kansas State University, 2013)
National parks reach out to millions of people each year by offering a number of recreational and educational experiences. People are exposed to new ideas and experiences in a national park that they may not get anywhere else. At Brown v. Board of Education National Historic Site in Topeka, Kansas, the National Park Service (NPS) compels visitors to step into the shoes of African American students in a segregated elementary school through the use of interpretive exhibits. This study was conducted to evaluate the effectiveness of the interpretive exhibits at Brown v. Board of Education National Historic Site. Most visitors sampled (91%) were visiting for the first time, indicating that the site does not have many repeat visitors. Race and the American Creed, the 30 minute film that plays in the auditorium, was found the most impactful exhibit by 34.3% of visitors surveyed. Expressions and Reflections, the temporary exhibit in the Kindergarten room, was the second most impactful exhibit, at 21.6% of visitors surveyed. The least impactful exhibit was the film Pass It On, at 0.9% of visitors surveyed. As a whole, visitors were most impacted by dynamic exhibits with a clear theme, while static exhibits and those that did not have a clear theme were not as impactful. This research will help guide Brown v. Board of Education National Historic Site staff as they contemplate future changes in the interpretive exhibits.
Keywords: National Historic Site; National Park Service; Recreation and tourism; Natural Resource Management; African American Studies (0296); History (0578); Natural Resource Management (0528)